Implementasi kebijakan pembacaan asmaul husna dalam membentuk karakter religius peserta didik (Studi kasus di SMP Tamaddun Roudlatul Qur’an Lampung) - Elisa, Reni; Aziz Q, Ikhwan; Hayati, Rina Mida (Kuras Institute, 2024)
Purpose − The purpose of this article is to describe the implementation of asmaul husna recitation in shaping the religious character of the learners. In the world of education, many efforts can be made to instill values of a religious character. Asmaul husna is one way to form religious character in students at Tamaddun Roudlatul Qur'an Junior High School. Method − This study uses qualitative field research methods. Meanwhile, the data collection uses interviews, observations and documentation. And using three stages of data analysis, in the form of data reduction, data presentation and conclusions Findings − The results of this study showed that the implementation of asmaul husna reading in shaping the religious character of students in Tamaddun Roudlatul Qur'an Junior High School was carried out every morning before the learning and teaching activities began, as well as accompanied by other religious activities such as dhuha prayer in the congregation, reading prayers before and after studying and praying dzuhur in the congregation. The supporting factors in shaping the religious character of students in Tamaddun Roudlatul Qur'an Junior High School lie in the role of parents, motivation of learners, role and efforts of teachers and supportive facilities. On the other hand, inhibiting factors are promiscuity, learners' lack of awareness, and different backgrounds.